Analysis Of The Influence Of Individual Characteristics And Motivation On The Performance Of Employees In The Bakery Business Unit Ketawawaka Waka Kota Siantar - Alfina Damayanti; Eli Delvi Yanti (Yayasan Multidimensi Kreatif, 2025)
The research analysis aims to determine whether individual characteristics and motivation affect employee performance at the Ketawawaka Waka Bread Business Unit, Siantar City. The data analysis technique used is the associative research method with the help of the SPSS version 19 program. This study uses multiple linear regression analysis. The sample in this study was 30 respondents. Primary data collection using a questionnaire. The results of the study indicate that individual characteristics have a Abstract - The research analysis aims to determine whether individual characteristics and motivation affect employee performance at the Ketawawaka Waka Bread Business Unit, Siantar City. The data analysis technique used is the associative research method with the help of the SPSS version 19 program. This study uses multiple linear regression analysis. The sample in this study was 30 respondents. Primary data collection using a questionnaire. The results of the study indicate that individual characteristics have a positive and significant effect on employee performance. This can be seen from the hypothesis test with a t-count value of 3.649> t-table of 2.05 with a significant value of 0.001 <0.05. Work motivation has a positive and significant effect on employee performance. This can be seen from the hypothesis test with a t-count value of 14.490> t-table of 2.05 with a significant value of 0.001 <0.05. Individual characteristics and motivation have a significant effect simultaneously on employee performance, this can be seen from the value of the F count of 394.654 which is greater than 3.35.